First record and range extension of the Galapagos slipper lobster, Scyllarides astori (Decapoda, Scyllaridae) in the central Pacific coast of Mexico mainland - Carbajal-López, Alberto; Rosende-Pereiro, Alejandro; Corgos, Antonio (Zootaxa, 2017)
The Galapagos slipper lobster Scyllarides astori was found for the first time off western Mexico mainland. A male and two female specimens were collected in south Jalisco and north Colima. This represents a new record from central Pacific coast of Mexico and a range extension of 700 km southwards, as the species was previously reported from the Gulf of California, 780 km eastwards from Revillagigedo Archipelago and 2400 km northwestwards from Isla del Coco and Galapagos Archipelago.